The Preaching Psychology Approach In Handling Student Individualism - Siti Rahma Harahap; Fithri Choirunnisa Siregar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The psychological approach to preaching is one approach that can be used among teenagers. For this reason, this research aims to use a preaching psychology approach in dealing with the problem of student individualism as a result of developments in science and technology. The research method used is a qualitative method with a descriptive analysis approach. Data was collected through observation, in-depth interviews, with the Miles and Huberman model as a data analysis technique. The results of the research show that the preaching psychology approach is an approach that can be used to deal with student individualism by understanding perceptions. The stages of understanding perception carried out are understanding perceptions about social life, providing the social environment as an experience. With the right knowledge and experience, they will slowly shape their personality and not be easily swayed.